A interdisciplinaridade entre as ciências e a educação física na visão de alunos do ensino fundamental e médio - Weber, Jacir Vicente (2009)
Education is passing through a transformation that transcends the classroom and searches to keep up with globalization. The era of information and integration between knowledge is being lived. Isolated learning has no value and no knowledge is pertinent if it is not related to some other knowledge. The present study investigated the existence of a possible multidisciplinary approach between Science and Physical Education for Elementary and High School students. The methodological profile used in this study was qualitative and a semistructured questionnaire was used to collect the data. Content Analysis was used for the data treatment, by which meaningful categories emerged. The research studied 800 subjects from Elementary and High School students from public and private schools of Santa Maria (between 10 and 17 of age). The questionnaire included the following question: Do you believe there is a relation between Science and Physical Education? Yes or No. Justify your response. Regarding the comparison between Elementary and High school, the students responses showed that the percentage of yes as an answer in Elementary and High School ranged of 50-60%. The percentage of no as an answer ranged between 15% and 33% for High School and Elementary School, respectively. The absence of response was about 26% for High School and 16% for Elementary School. Regarding the results of inferred categories from the yes answers about 33 to 38% of High and Elementary School students stated there is a relationship between physical activity with education, respectively. About 20% of Elementary School students answered that physical activity is related with different characteristics (strength, metabolism and acceleration), whereas around 10% of High School students share the same opinion. Regarding the interconnection between body and mind, around 20% of High school and Elementary School students had similar opinions. About 10% of Elementary School students associate physical activity to physical education as something good to relax from the studies , while in High School this percentage increased about 20%. Around 7% of Elementary School students relate the physical education as elements of chemical reactions, while 14% of High School students have this kind of thought. On the inferred categories from the no responses, approximately 64% and 32% of the High School and Elementary school students, respectively, have the opinion that there is a dissolution between body and mind at school environment. Around 40% of Elementary School students answered no with no justification, being that this percentage is just 9% on High School. Approximately 13% of Elementary School and 9% of High School students see physical education as something good and healthy. About 10% of students see physical education as optional. Besides, around 10% of Elementary School students report that there is no interdisciplinarity between the areas of Science and Physical Education at school, but just half of this High School students percentage shared the same opinion. A perception that points to some interdisciplinary relation between Physical Education and Science was inferred. This relation can be potentiated from the effort and flexibility of professionals from both areas of knowledge, in the search of new teaching manners, instead of just passing disconnected contents, which does not provide to the students the space for discussions and critics about the programmatic contents ministered in the school.